Crude extracts of Magnolia schiedeana Schltdl. for the control of phytopathogenic bacteria - Ramírez-Reyes, Thalía; Flores-Estévez, Norma; Luna-Rodríguez, Mauricio; Noa-Carrazana, Juan Carlos; Sánchez-Velásquez, Lázaro R.; Trigos-Landa, Ángel (Instituto de Ecología, A.C., 2016)
Bactericidal effect was assessed in crude extracts of different tissues of Magnolia schiedeana about the phytopathogenic bacteria Pectobacterium carotovorum and Pseudomonas cichorii. The tissues studied were polifolicule, seed, bark (obtained from adult specimens and young specimens), flower and leave (from both adult and young specimens as well), using as solvents ethyl acetate and ethanol. The extracts that showed bacterial inhibition were obtained one with ethyl acetate from floral tissue, which did not equaled the inhibiting properties of a commercial antibiotic (tetracycline, 5 µg/µl) on P. cichorii (p < 0.001); and the other was floral ethanol extract that inhibited P. carotovorum in the same proportion as the antibiotic (p = 0.079).